Morphological identification of ticks (Acari: Ixodidae) infesting donkeys (Equus asinus) in Maputo Province, Mozambique - Esculudis, Carolina; Matos, Carlos De; Cala, Aida; Sungirai, Marvelous; Madder, Maxime; Mapatse, Milton (Springer, 2022)
Donkeys (Equus asinus) are rustic animals, but in Africa's poorest regions, they can present multiple health problems, including tick infestation. The study's objective was to determine the species composition of ticks that infest donkeys in Maputo Province (Mozambique). Ticks were collected in five conveniently selected southern districts of Maputo Province (Moamba, Matutuíne, Marracuene, Boane, and Matola) and were identified to species level using a stereoscopic microscope with the aid of dichotomous identification keys. In total, 500 ticks were collected from all 88 selected donkeys. Three genera of ticks were identified, namely Rhipicephalus (97.2%; 486/500), Amblyomma (2.2%; 11/500), and Hyalomma (0.6%; 3/500). Seven species were identified, of which Rhipicephalus evertsi evertsi with 50.4% (252/500) was the most prevalent, followed by Rhipicephalus appendiculatus (27.4%; 137/500), Rhipicephalus turanicus (11.6; 10/500), Rhipicephalus (boophilus) microplus (6.8; 20/500), Amblyomma hebraeum (2.2%; 11/500), Rhipicephalus sanguineus (1%; 5/500) and Hyalomma truncatum (0.6%; 3/500). Rhipicephalus evertsi evertsi occurred in all locations, whereas Hyalomma truncatum occurred only in the Boane district. Males were the most prevalent (67.2%; 336/500). The study revealed that donkeys in Maputo Province were infested with seven tick species of which R. evertsi evertsi was the main species.